Blockchain-based Trust, Transparent, Traceable Modeling on Learning Recognition System Kampus Merdeka - Irawan Afrianto; Andri Heryandi; Sufa Atin (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2023)
Kampus Merdeka is an evolution of education in Indonesia that accommodates various changes. The existence of a mechanism that includes various actors in it makes Kampus Merdeka have many new outcomes which must be recognized by all stakeholders who need it. Blockchain technology and smart contract offer the ability to build trust between all actors in the Kampus Merdeka activities with their transparent nature and reliable, immutable data storage capabilities. Every stage that occurs in it can be traced from upstream to downstream. This study aims to design an architectural model of a blockchain system for the learning recognition system Kampus Merdeka. It uses the analyticalstudy to identify the possible problems and the stakeholders involved and design the model solution proposed. As a result, it proposed the type of blockchain and the most suitable architecture for use in the learning recognition system Kampus Merdeka. In this study, the blockchain model is proposed as a mechanism for identifying and recognizing learning outcomes in the Kampus Merdeka environment more securely, challenging to modify, and traceable by all parties to ensure the authenticity of the learning outcomes. Furthermore, it can be recognized by all parties in it.